2018
DOI: 10.1186/s13550-018-0405-5
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of 68Ga-NODAGA-RGD, as compared with 18F-fluorodeoxyglucose, in experimental rodent models of engrafted glioblastoma

Abstract: BackgroundTracers triggering αvβ3 integrins, such as certain RGD-containing peptides, were found promising in previous pilot studies characterizing high-grade gliomas. However, only limited comparisons have been performed with current PET tracers. This study aimed at comparing the biodistribution of 18F-fluorodeoxyglucose (18F-FDG) with that of 68Ga-NODAGA-RGD, an easily synthesized monomeric RGD compound with rapid kinetics, in two different rodent models of engrafted human glioblastoma.MethodsNude rodents be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Our viewpoint was consistent with previous reviews, that 18 F-RGD is a promising tracer for tumor angiogenesis imaging and monitoring anti-angiogenesis therapy in solid tumor [25,26]. In Sibel lsal's study, they also veri ed that the expression of integrin αvβ3, which are targeted by RGD-based peptides tracer, was associated with cell proliferation in glioblastoma [27].…”
Section: Discussionsupporting
confidence: 91%
“…Our viewpoint was consistent with previous reviews, that 18 F-RGD is a promising tracer for tumor angiogenesis imaging and monitoring anti-angiogenesis therapy in solid tumor [25,26]. In Sibel lsal's study, they also veri ed that the expression of integrin αvβ3, which are targeted by RGD-based peptides tracer, was associated with cell proliferation in glioblastoma [27].…”
Section: Discussionsupporting
confidence: 91%
“…All HNSCC primary tumors, lymph nodes, and metastases detected on 18 F-FDG PET/CT images were also seen with the angiogenesis radiotracer. Only few studies have been conducted in humans; while Haubner et al [20] demonstrated that 68 Ga-NODAGA-RGD uptake was not sufficient to be used in patients with hepatocellular carcinoma, other authors reported sufficient uptake for diagnostic purpose in human xenografts of esophageal carcinoma, melanoma, and glioblastoma [18,21]. As both 68 Ga-NODAGA-RGD and 18 F-Galacto-RGD demonstrated similar preclinical results [22], our results are in line with the previous work by Beer et al [8], who concluded that thanks to its significant uptake, 18 F-Galacto-RGD might be used for the assessment of angiogenesis and for planning and response evaluation of α v β 3 targeted therapies in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-NODAGA-RGD uptake beyond 18 F-FDG avid areas could thus reflect the presence of the formation of neovessels. Isal et al [21] demonstrated that tumor areas with high 68 Ga-NODAGA-RGD uptake also exhibited the highest rates of cell proliferation and integrin expressions irrespective of cell density in engrafted glioblastomas. This seems to be different in HNSCC, as we did not find any significant association between tracers' uptake and HNSCC grade.…”
Section: Discussionmentioning
confidence: 99%
“…To this purpose we conducted a one-to-one comparison of tracers to assess the clinical potential of PET/CT images were also seen with the angiogenesis radiotracer. Only few studies have been conducted in humans; while Haubner et al [20] demonstrated that 68 Ga-NODAGA-RGD uptake was not sufficient to be used in patients with hepatocellular carcinoma, other authors reported sufficient uptake for diagnostic purpose in human xenografts of esophageal carcinoma, melanoma and glioblastoma [18,21]. As both 68 Ga-NODAGA-RGD and 18 F-Galacto-RGD demonstrated similar preclinical results [22], our results are in line with the previous work by Beer et al [8], who concluded that thanks to its significant uptake, 18 F-Galacto-RGD might be used for the assessment of angiogenesis and for planning and response evaluation of α v β 3 targeted therapies in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-NODAGA-RGD uptake beyond 18 F-FDG avid areas could thus reflect the presence of the formation of neovessels. Isal et al [21] demonstrated that tumor areas with high 68 Ga-NODAGA-RGD uptake also exhibited the highest rates of cell proliferation and integrins expressions irrespective of cell density in engrafted glioblastomas. This seems to be different in HNSCC, as we did not find any significant association between tracers' uptake and HNSCC grade.…”
Section: Discussionmentioning
confidence: 99%